The Expression Of Insulin-like Growth Factors And Their Receptors At Preimplant Ation Stage In Reproductive Tissue Of Diabetic Mouse - Zakaria, Rahimah (2006)
Kami menghipotesis bahawa embrio praimplantasi yang berkembang dalam persekitaran diabetes mengalami kekurangan faktor pertumbuhan tertentu.